Educating for Biocultural Diversity and Sustainable Development in First Years of Schooling: An Analysis of Documents From the Portuguese Educational System - Batista, Bruna Fonseca; Andrade, Ana Isabel (Frontiers in Education, 2021)
Educating for sustainable development can encompass different perspectives and possibilities that enable the achievement of the goals of (more) sustainable development, as predicted by the United Nations for 2030. This type of education also involves a humanist and citizenship education, which can prepare children, youth, and adults to face current and future challenges, local and global, as actors in building a better future. We believe, however, that for education to bear fruit, it is important that children, from the first years of schooling (primary education), can be in contact with different perspectives, people, ways of learning, and worldviews, locally contextualized and relevant, with strong links to the natural and social environment involving their communities, such as education must value linguistic and cultural diversity, without forgetting biodiversity and the influences they exert on the education of individuals. Thus, looking at an education that encompasses the relationships among linguistic, cultural (stories, celebrations, heritage, artefacts, relationships, and behaviors between people, etc.), and biological diversity, the present study aimed to understand how biocultural diversity is present in the main normative-legal documents that govern education for the first years of schooling in the Portuguese educational system and, above all, if its existence is considered in education for sustainable development. For this study, seven guiding documents of the Portuguese educational system, and primary education in particular (education that includes the interval from the 1st to the 4th year and the average age-groups of 5–10 years of age), were analyzed, and the results show a gap regarding the presence of biocultural diversity, which points to an incomplete perspective of education for sustainable development, forgetting languages, cultures, and individuals.